Multibiometrics Approach on Biometric Passport Pictures by Using Fingerprint Minutiae Points - Aygun, Sercan; Akcay, Muammer (IEEE, 2016)
Biometrics has its own popularity in recent years especially in engineering field. Biometrics related researches have been increasingly handled by scientists to achieve more secure and high performed systems. In low level or higher level designs, there are two basic criterion initially to be considered: area and speed. Hardware designs like in smart cards require less complex circuits in the sense of area. In this study, there will be system related biometric research and implementations by only considering the high level designs. Module based high level design is implemented which includes feature extraction and decision modules. In the first, biometric feature extraction together with relatively new techniques is handled. Fingerprint identification and face recognition are the first part interests by using new operators to reduce the operation complexity. In the second module, the decision of the authentication will be handled by using multi biometrics. Fingerprint and face arc popular biometrics. In the feature extraction phase, new method to obtain features is used both for the finger and for the face. New image processing operator, Relational Bit Operator (RBO) is for the face biometry. Besides, Angle Invariant Fingerprint Features Matching Technique (AIFM) is for fingerprint matching. This paper presents the introduction to biometric systems together with literature review. After the design issues are presented, the test results related to biometric authentication metric is added in the final draw of the paper.
Keywords: angle invariant fingerprint matching; decision level fusion; multibiometrics; relational bit operator; Computer Science; Engineering